Determinasi Kinerja ASN: Analisis Beban Kerja, Kompensasi, dan Mediasi Semangat Kerja - Sari Sakarina; Sri Lestari; Nasir Nasir (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the determinants of civil servant performance by examining the effects of workload and compensation, with work motivation as a mediating variable, at the Regional Secretariat of South Sumatra Province. The research employed a quantitative approach with an explanatory design to test the proposed hypotheses. The sample was selected using proportional random sampling to ensure representative participation of civil servants across units. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to evaluate both the measurement and structural models.The findings reveal that workload and compensation significantly influence both work motivation and employee performance. Work motivation has a positive and significant effect on performance and serves as a partial mediator in the relationship between workload and compensation on performance. This indicates that appropriate workload management and fair compensation not only directly enhance performance but also indirectly improve it by strengthening employees’ motivation. The R² results demonstrate that the model possesses moderate to strong explanatory power in predicting civil servant performance. Overall, the study underscores the importance of balancing workload distribution and implementing performance-based compensation systems to foster higher motivation and optimize organizational performance.